2003
DOI: 10.2355/isijinternational.43.1733
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Optical DTA for Morphological Transition in the Al2O3-YAP-ZrO2 Metastable Eutectic System

Abstract: This paper presents an optical DTA apparatus which is capable to examine the solidification behavior of the Al 2 O 3 -based materials. A direct current through the two Mo crucibles effectively heats specimen and reference up to 2 400 K. The small heat capacity of the crucible and the specimen enabled a cooling rate up to the order of 10 2 K/s. Since accuracy of temperature measurement by two two-color pyrometers was not affected by emissivity change to phase transformation, exothermic and endothermic heats in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[1][2][3] Theoretical models not to take macro steel flow into account, have also been published, 4) and a new research has demonstrated that the thermal conductivity of particles is important for entrapment probability. 5,6) Al 2 O 3 particles are usually observed on the surface of bubbles in cast steel, where they seem to coagulate. This suggests that the presence of bubbles accelerates coagulation and thus encourages the formation of larger Al 2 O 3 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Theoretical models not to take macro steel flow into account, have also been published, 4) and a new research has demonstrated that the thermal conductivity of particles is important for entrapment probability. 5,6) Al 2 O 3 particles are usually observed on the surface of bubbles in cast steel, where they seem to coagulate. This suggests that the presence of bubbles accelerates coagulation and thus encourages the formation of larger Al 2 O 3 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the method is illustrated by analysis of heat treatment of thin colloidally processed xerogel plates. Yasuda et al (10) present an optical DTA apparatus capable of examining the solidification behavior of the Al 2 O 3 -based materials. A direct current through the two Mo crucibles effectively heats specimen and reference up to 2400 K. Two-color pyrometers are used for evaluating the temperature changes.…”
Section: Methods Development and Calibrationsmentioning
confidence: 99%